Three is a crowd? : acquiring Portuguese in a trilingual environment - Cruz-Ferreira, Madalena, 1952- (Child language and child development, 2006)
The book describes three siblings' apportioning of linguistic and cultural space among three languages: Portuguese, Swedish and English. Parallel strategies accounting for monolingual and multilingual language management shape a truly illuminating picture of child linguistic competence.